Stille Geburt: Wie das Gesundheitspersonal die Kommunikation mit Eltern totgeborener Kinder erlebt: Ein Scoping Review - Schröder, Rebecca (Tectum Verlag, 2024)
It is imperative that healthcare staff are able to communicate effectively and empathetically. Research has demonstrated that the manner in which the death of a child is conveyed can have a significant impact on the mental health of the parents. However, there is a pressing need for further investigation into the communication experiences of the accompanying staff. Rebecca Schröder employs a systematic literature review to examine how healthcare professionals experience (non)verbal communication with parents of stillborn children. She then presents the findings from the parents' perspective. The findings of this study provide a foundation for further research, as well as for the development of training and educational programs that are urgently needed.